CMOS integrated circuits for millimeter-wave imaging applications - Feng, Guangyin (2016)
In the first part of this research, two wideband LNAs for mm-wave imaging applications are presented. One is a five-stage cascode LNA based on peak-gain distribution technique. By distributing peak gains of the first four stages at two frequency points, the five-stage cascode LNA exhibits 3-dB bandwidth of 21.5 GHz. The other is a three-stage cascode LNA based on a novel pole-converging technique. The prototype demonstrates 3-dB bandwidth of 30 GHz. Second, a direct-detection Dicke receiver with a switchable dual-path LNA (SDP-LNA) is proposed. Pole-converging technique is adopted in the design of the SDP-LNA. Based on the SDP-LNA, a direct-detection Dicke receiver is implemented, which achieves NETD of 0.65 K with power consumption of 52.6 mW. Third, an ultra-low-power and low-cost mm-wave imaging receiver based on charge-accumulation super-regenerative reception is presented, which significantly improves receiver responsivity and sensitivity. The prototype achieves 0.21-K NETD with power consumption of 0.9 mW.